A REVIEW OF SCIENTIFIC RESEARCH ON THE OPTIMIZATION OF THE DRAFTING ZONE OF THE SLIVER MACHINE - Suxrob Axmadjanov; Boburshox Adashev; Sherzod Korabayev (Innovate Conferences, 2025)
This article presents an analytical overview of scientific studies on optimizing the drafting zone of the sliver machine. It evaluates the impact of various technological and mechanical parameters — such as draft ratio, roller spacing, and applied pressure — on yarn quality, evenness, and hairiness. The findings demonstrate the importance of precise control over the drafting zone settings to ensure structural stability of the sliver, ultimately enhancing the quality of the produced yarn. These insights are critical for improving textile production efficiency and final product performance.
Keywords: Sliver machine, drafting zone, yarn quality, unevenness, process parameters, roller pressure, fiber motion